KAJIAN KURIKULUM JURUSAN PENDIDIKAN TEKNIK ELEKTRO FAKULTAS TEKNIK UNIVERSITAS NEGERI YOGYAKARTA MENGACU PADA KERANGKA KUALIFIKASI NASIONAL INDONESIA - Edy Supriyadi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThis reserach aims at evaluating and completing the curriculum of Electrical Engineering EducationDepartment, Faculty of Engineerinng, Yogyakarta State University to meet the need of stakeholders as well asthe development of science and technology. The method in investigating and developing the currriculum wasreferred to Indonesian National Qualification Framework for Electrical Engineering and Electrical EngineeringEducation. This study is a research evaluation on the implementation of curriculum with CIPP model. Thecurriculum development was using content analysis and discussion. The research result showed that, in general,the implementation of Curriculum 2009 for Electrical Engineering Education Department could be categorized as“appropriate” (Good) according to the respondents of lecturers or alumnae and “quite appropriate” accordingto the students. There were few weaknesses either the curriculum content or its implementation especially on theaspects of Input, Process, and Product. Based on the evaluation result on the curriculum implementation, IndonesianNational Qualification Framework as well as vision, mission and the purpose of Electrical Engineering EducationDepartment, it was found that both the draft for curriculum framework and the competence that should be masteredby the graduates of Electrical Engineering Education (Bachelor level) and Electrical Engineering (Diploma level)need to be reviewed and validated. Those actions should be conducted in order to produce a curriculum designwhich had relevance as well as adequate quality and usefulness for students, society, and corporate world.Keywords: curriculum,Indonesian National Qualification Framework (INQF)